1982
DOI: 10.1017/s0043174500026278
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress Increases Alkaloid Concentrations in Threadleaf Groundsel (Senecio longilobus)

Abstract: The influence of water stress on toxic alkaloid concentrations in threadleaf groundsel (Senecio longilobus Benth.) was investigated in a controlled environment by monitoring leaf xylem water potential during a 32-day period, and then analyzing for alkaloid concentration by plant part. Total plant alkaloid concentration increased with increasing severity of water stress. The most severe water stress (−2.0 MPa) for the 32-day period increased alkaloid concentration by 4.6 times, compared to the least stress impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The effects of latex and foliar cardenolides under drought may be due both to induced physiological processes as well as the reduced biomass of drought-stressed plants; the latter being relevant to the fact that we measure cardenolides as a concentration on a dry mass basis, and that larger plants typically exude more latex. Across other systems, plant defense compounds often increase in response to drought, but water content often declines (Briske andCamp 1982, English-Loeb et al 1997). Accordingly, our results with milkweed may reflect the general pattern of increased secondary metabolite concentrations under drought, but the reduced latex may simply depend on water availability.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of latex and foliar cardenolides under drought may be due both to induced physiological processes as well as the reduced biomass of drought-stressed plants; the latter being relevant to the fact that we measure cardenolides as a concentration on a dry mass basis, and that larger plants typically exude more latex. Across other systems, plant defense compounds often increase in response to drought, but water content often declines (Briske andCamp 1982, English-Loeb et al 1997). Accordingly, our results with milkweed may reflect the general pattern of increased secondary metabolite concentrations under drought, but the reduced latex may simply depend on water availability.…”
Section: Resultsmentioning
confidence: 99%
“…a/. , 1977 and alkaloids in particular (Marten & Frelich 1977;Majak et al 1979;Briske & Camp 1982), the PA content of H. europaeum declined independently of rainfall and plant growth through the growing season (Table 2; Fig. 4).…”
Section: Discussionmentioning
confidence: 95%
“…So far, it is not clear what type and combination of environmental factors alters PA concentration in different Senecio species. In some studies nutrient availability and water stress were shown to affect alkaloid concentration, while in others no such interactions were found (Briske & Camp, 1982;Toppel et al, 1988;Vrieling and van Wijk, 1994;Brown & Molyneux, 1996).…”
Section: Discussionmentioning
confidence: 99%